The effect of educational intervention based on the health action model on safe use of pesticides in Iranian farmers - Maryam Nasrabadi; Mahdi Gholian Aval; Mohammad Tajfard; Nooshin Peyman; Seyedeh Belin Tavakoly Sany; Najmeh Khodadadi (Scientific Reports)
Abstract The health risks associated with excessive pesticide use have adversely affected agricultural products and human health, raising global concerns about the safety of consumers and agricultural workers. Therefore, this study aimed to investigate the impact of an educational intervention based on the health action model (HAM) on summer workers’ safety behaviors regarding pesticide use. The present quasi-experimental study involved an experiment and a control group. A multi-stage random cluster sampling method was employed to select 100 farms from a total of 1000 summer vegetable farms in Mashhad through a simple randomization process. Then, 300 eligible workers were selected and allocated into an experimental group and a control group. The educational intervention consisted of two focus group discussion sessions and eight training sessions making educational training based on the HAM. Data analysis was conducted using SPSS 16, and tests were chosen based on the distribution of variables. Both parametric and equivalent non-parametric tests were applied at a significance level of 0.05. Following the intervention, the mean scores of all constructs in the experimental group improved significantly, with the exception of the normative system. The educational intervention-based HAM had a significant effect (p < 0.05) on safety behavior outcomes and all knowledge-related dimensions (safe place and pesticide use, personal safety during spraying, personal safety after spraying, pesticide side effects) in the intervention group compared with the control group after the intervention, and in their change from baseline to follow-up in all scores. The mean score of safety behavior in the pre-intervention increased from 5.2 ± 1.27 to 8.1 ± 0.82 in the follow-up. However, no statistically significant difference was found in the control group. The educational program based on HAM and knowledge-related dimensions significantly improved safety behaviors among farmers and agricultural workers regarding pesticide use. This study emphasizes the need for implementing theory based- educational programs for diverse agricultural workers to enhance safety practices and reduce health risks associated with pesticide exposure.